Analisis Faktor Yang Memengaruhi Penggunaan Mata Uang Lokal Dalam Perdagangan Antara Indonesia, Malaysia, Dan Thailand - Makarim, Moch. Amil Labib; Putri Ardaneswari, Aretha; Hutahaean, Olyvia (Politeknik Keuangan Negara STAN, 2024)
The Local Currency Settlement (LCS) is widely used in trade between countries in the ASEAN region. However, not all collaborations use this method. This research will analyze several factors that influence the LCS by using qualitative methods. The research was localized in three countries: Indonesia, Malaysia, and Thailand. The results show that there are influencing factors such as dollarization effects, and economic and political benefits for countries implementing LCS. It turns out that the LCS also has shortcomings, such as no guarantee of political stability between cooperating countries and an unavoidable trade balance deficit. The advantages and disadvantages of LCS are proportional to its application. There needs to be increased cooperation between countries implementing LCS and stricter regulations to minimize potential losses in the transactions.